Resilient African Feed and Fodder Systems (RAFFS) Project - MacOpiyo, Laban (African Union Interafrican Bureau for Animal Resources, 2025)
Presented at the Jameel Observatory drylands food security and resilience early action research and evidence dialogue, Addis Ababa, Ethiopia, 15-16 May 2025